To solve this system of equations by substitution, we can solve one equation for one variable and substitute that expression into the other equation.
Let's solve the second equation for x:
x - 2y = 11
x = 2y + 11
Now we can substitute this expression into the first equation:
-7(2y + 11) - 2y = -13
Simplifying, we get:
-14y - 77 - 2y = -13
-16y - 77 = -13
Adding 77 to both sides:
-16y = 64
Dividing both sides by -16:
y = -4
Now we can substitute this value of y back into the second equation to find x:
x - 2(-4) = 11
x + 8 = 11
x = 11 - 8
x = 3
So the solution to the system of equations is x = 3 and y = -4.
systems of equations by substitution.
−7x−2y=−13
x−2y=11
1 answer